Molecular identification of two Eimeria species, E. uekii and E. raichoi as type B, in wild Japanese rock ptarmigans, Lagopus muta japonica - 芝原, 友幸; シバハラ, トモユキ; SHIBAHARA, Tomoyuki (International Journal for Parasitology: Parasites and Wildlife, 2018)
journal article